A hybrid protocol CLAG-M, a possible player for the first-line therapy of patients with mixed phenotype acute leukemia. A Polish Adult Leukemia Group experience - Karasek, Magdalena; Armatys, Anna; Skarupski, Marek; Bołkun, Łukasz; Budziszewska, Katarzyna; Drozd-Sokołowska, Joanna; Zarzycka, Ewa; Mensah-Glanowska, Patrycja; Gajewska, Małgorzata; Hałka, Janusz; Kopacz, Agnieszka; Prejzer, Witold; et al. (Frontiers in Oncology, 2024)
Introduction: Mixed phenotype acute leukemia (MPAL) is a rare disease with a poor prognosis. So far, no standard approach has been established as the "know-how" of MPAL is based only on retrospective analyses performed on small groups of patients.In this study, a retrospective analysis of the outcome of MPAL adult patients included in the PALG registry between 2005 and 2024 who received CLAG-M hybrid protocol as induction or a salvage therapy was performed. Results: Sixteen of 98 MPAL patients received CLAG-M: 8 as first-line and 8 as salvage therapy. In the first line, two patients achieved partial response (PR), and six achieved complete remission (CR), of whom 4 successfully underwent allogeneic hematopoietic stem cell transplantation (alloHSCT). Two patients who did not undergo alloHSCT promptly relapsed. Within the whole group, the overall response rate (ORR) was 75% (n=12/16). With the median follow-up of 13 months, 6 out of 8 patients remain in CR, however, two of them died due to acute graft versus host disease. Out of eight patients who received CLAG-M in the second line, 4 patients (50%) obtained CR. The alloHSCT was conducted in 7 cases, 6 of them in CR. Only two patients remained in CR at the time of the last followup.The tolerance of the treatment was good. The median time for severe neutropenia was 22 days (range 16-24) and 17 days for severe thrombocytopenia (range 12-24). Overall, infections in grades 3-4 were observed in 12 cases; all infections presented successful outcomes.Conclusions: CLAG-M is an effective first-line and salvage regimen in MPAL, with an acceptable safety profile. Early achievement of CR with prompt alloHSCT allows for satisfying disease control.